The Role of Self-Efficacy in the Thesis-Writing Experiences of Undergraduate Honors Students - Medaille, Ann; Beisler, Molly; Tokarz, Rayla; Bucy, Rosalind (Teaching and Learning Inquiry, 2022)
Writing a thesis is often the culminating experience for undergraduate students enrolled in university honors programs in the United States. Because writing a thesis is one of the most difficult academic tasks that an undergraduate student may undertake, it requires a high level of self-efficacy, or belief in one’s capabilities to achieve certain results. However, the factors that contribute to students’ efficacy expectations when writing a thesis are not fully understood. This qualitative study followed 11 honors students over the course of several months in order to understand their experiences as they completed their theses. Data was gathered through a series of four questionnaires and two interviews. Analysis revealed six themes: previous research experiences, emotions, project timelines, structure, advisors, and support networks. These themes suggest that students’ abilities to manage their emotions and employ self-regulatory strategies play a critical role in their self-assessments of efficacy during work on challenging academic tasks, findings which have implications for a variety of academic programs and campus support services. In addition, this study reveals that faculty mentoring of undergraduate students may require greater attention to cultivating emotional awareness and regulation than does the mentoring of graduate students.